Optimizing formulation and development of amlodipine-indapamide bilayer film-coated tablets with in vitro dissolution equivalence to a reference drug - Duyen Thi My Huynh; Tuan Duc Nguyen; Quyen Hoang Nguyen; Tai Nguyen Thanh Dao; An Doan Quynh Nguyen; Nguyen Ngoc Khoi Nguyen; Mai Thi Anh Nguyen; Lan Kim Huynh; Minh-Ngoc Thi Le; Tri Vinh Nguyen; Phuoc Huu Le; Son Thanh Khuu (Pharmacia)
This study aimed to develop and optimize a bilayer tablet containing immediate-release amlodipine and sustained-release indapamide for the treatment of hypertension. Using BCPharSoft OPT software, individual layer formulations were optimized: 8.63% croscarmellose sodium for the amlodipine layer and 32.41% HPMC K15M with 4.51% PVP K30 for the indapamide layer. The final bilayer tablets exhibited hardness between 230 N and 260 N and a 3% weight gain after film coating, which had no significant effect on drug release. A validated HPLC–DAD method, following ICH guidelines, confirmed the accurate quantification of both drugs across pH 1.2, 4.5, and 6.8. The method demonstrated high specificity, linearity, accuracy, precision, and robustness. Overall, the formulation achieved in-vitro dissolution equivalence to a reference commercial product.